Engineering Modernity:: Hydroelectric Development in New Brunswick, 1945-1970 - Kenny, James; Secord, Andrew (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2010)
Abstract This study explores the origins of the Mactaquac multi-purpose hydroelectric development, a high modernist mega-project built along New Brunswick’s St. John River during the 1960s. Informed by Tennessee Valley Authority multi-purpose planning and supported by the availability of federal regional development funds, the New Brunswick Electric Power Commission (NBEPC) transformed Mactaquac from a simple dam into a rural modernization scheme. When a vocal opposition emerged, led by the Association for the Preservation and Development of the Saint John River in its Natural State, NBEPC engineers launched an aggressive – and ultimately successful – public relations strategy designed to silence Mactaquac’s critics by linking the project with progress and modernity.